2005
DOI: 10.1152/ajpregu.00386.2005
|View full text |Cite
|
Sign up to set email alerts
|

Integration in the PVN: another piece of the puzzle

Abstract: THE PARAVENTRICULAR NUCLEUS (PVN) of the hypothalamus is a major integratory region in the hypothalamus that helps maintain homeostasis. Functionally, the PVN is involved in regulation of food intake, responses to stress, modulating metabolic rate, thermoregulation, and regulation of cardiovascular function and the autonomic nervous system (2,4,7,14,30,34,40). It is unique in that in contains primarily estrogen receptor ␤-receptors that regulate transcripts for vasopressin and oxytocin and also affect the func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 44 publications
4
40
0
3
Order By: Relevance
“…The PVN is involved in coordination of respiratory and cardiovascular responses to a number of stimuli (39,53), including those from peripheral chemoreceptors (41,48). Previously, it has been shown that bilateral microinjection of glutamate into the PVN in urethane-anesthetized vagotomized and ventilated rats caused an increased in peak D EMG activity and D EMG frequency discharge.…”
Section: Physiological Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The PVN is involved in coordination of respiratory and cardiovascular responses to a number of stimuli (39,53), including those from peripheral chemoreceptors (41,48). Previously, it has been shown that bilateral microinjection of glutamate into the PVN in urethane-anesthetized vagotomized and ventilated rats caused an increased in peak D EMG activity and D EMG frequency discharge.…”
Section: Physiological Studiesmentioning
confidence: 99%
“…It receives inputs from visceral receptors, circulating hormones and limbic circuits and transmits information to multiple CNS sites (11,53), including cell groups regulating respiratory drive (27,30,58) and sympathetic outflow (6,13,24,26,27,41,48).…”
Section: Introductionmentioning
confidence: 99%
“…THE PARAVENTRICULAR NUCLEUS (PVN) of the hypothalamus integrates multiple forebrain and brain stem inputs to regulate the autonomic nervous system via outputs that ultimately converge with focal brain stem nuclei, such as the rostral ventrolateral medulla, as well as preganglionic sympathetic neurons in the spinal cord (7,27,29,32). While the contribution of the PVN and its connections to basal sympathetic tone at rest in normal animals is minimal, it appears to drive increased sympathetic activity in such pathophysiological states as hypertension, heart failure, and water deprivation (7,27).…”
mentioning
confidence: 99%
“…While the contribution of the PVN and its connections to basal sympathetic tone at rest in normal animals is minimal, it appears to drive increased sympathetic activity in such pathophysiological states as hypertension, heart failure, and water deprivation (7,27). Moreover, the PVN mediates, in part, autonomic responses to diverse homeostatic challenges, such as changes in food intake, blood volume, stress, and body temperature (29). However, whether and how the PVN can also influence the regulation of the baroreceptor reflex is currently unclear.…”
mentioning
confidence: 99%
“…Esta localização no meio do diencéfalo margeando uma região de grande difusão de líquido céfalo-raquidiano torna o PaV a maior região integradora do hipotálamo, envolvida na manutenção da homeostase (Schlenker, 2005 (Reghunandanan, Reghunandanan, 2006). Funcionalmente, o…”
Section: Discussionunclassified